Beyond Recidivism: exploring the Predictive Validity of a Correctional Risk Assessment Tool on Offender Victimization - McCafferty, James T. (The prison journal, 2017)
A vast body of past research on correctional risk assessment instruments supports their validity in predicting measures of recidivism across diverse offender population samples. Despite similarities in the risk factors for victimization and offending, little is known about whether the generalizability of these actuarial tools can be extended beyond recidivism to predict victimization measures as well. Utilizing a sample of approximately 1,900 recently released male and female prisoners, this study examined whether measures of risk drawn from the Level of Service Inventory-Revised: Screening Version (LSI-R:SV) could predict one’s risk of victimization. Analyses provide evidence that the risk scores and levels were significantly related to both recidivism and victimization. Policy and prevention implications for correctional assessment and offender treatment are discussed.